Pengaruh Perhatian Orangtua Dan Lingkungan Sosial Terhadap Prestasi Belajar Aqidah Akhlak - Rosada, Ulfa Danni (STKIP Andi Matappa, 2019)
The purpose of this study were (1) To determine the effect of parents' attention on learning achievement Aqeedah Morals grade students at SMA Muhammadiyah Piyungan, (2) To determine the influence of social environment on learning achievement Aqeedah Morals grade students at SMA Muhammadiyah Piyungan (3) to determine the influence of parental and social environment on learning achievement Aqeedah Morals grade students at SMA Muhammadiyah Piyungan. The research method uses a quantitative approach. Data analysis technique uses multiple linear regression analysis. The results and conclusions obtained (1) There is the influence of parents' attention on learning achievement Aqeedah Morals grade students at SMA Muhammadiyah Piyungan, (2) There is the influence of social environment on learning achievement Aqeedah Morals grade students at SMA Muhammadiyah Piyungan, (3) There is the influence of parental and social environment on learning achievement Aqeedah Morals grade students at SMA Muhammadiyah Piyungan.